2020
DOI: 10.3389/fphar.2020.00911
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a New Phenyl Chlormethine-Quinazoline Derivative, a Potential Anti-Cancer Agent, Induced Apoptosis in Hepatocellular Carcinoma Through Mediating Sirt1/Caspase 3 Signaling Pathway

Abstract: Quinazoline derivatives display multiple pharmacological activities and target various biological receptors. Based on the skeleton of quinazoline core, we designed and synthesized three new quinazoline-phenyl chlormethine conjugates (I-III) bearing a Schiff base (C = N) linker, and investigated their anti-tumor effects on HepG2-xenografted tumor and human cancer cell line HepG2. Among these compounds, compound II showed better inhibitory effect against HepG2 cells. In the present study, TUNEL staining, western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…To apply the chemosensor L in living cells for the fluorescence imaging detection of Zn 2+ , we first tested the cytotoxicity of L against HepG2 cells using the MTT assay . The results showed that L had a low cell inhibitory rate (Figure S48) and could be used as a biocompatible probe for the cellular imaging of Zn 2+ .…”
Section: Results and Discussionmentioning
confidence: 99%
“…To apply the chemosensor L in living cells for the fluorescence imaging detection of Zn 2+ , we first tested the cytotoxicity of L against HepG2 cells using the MTT assay . The results showed that L had a low cell inhibitory rate (Figure S48) and could be used as a biocompatible probe for the cellular imaging of Zn 2+ .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Many caspase‐3 activation‐mediated apoptosis inducers for potential cytotoxicity have been reported till date (Jain et al., 2012, 2013, 2019; Jain, Pattnaik, et al., 2017; Kumar et al., 2021; Lv et al., 2020; Vaidya et al., 2020a, 2020b; Vaidya, Pathak, et al., 2020). Numerous SAR and QSAR studies were reported in favor to search of these compounds (Mansouri et al., 2020; Jain, Vaidya, et al., 2017; Şenkardeş et al., 2021; Vaidya et al., 2014).…”
Section: Caspase‐3 Activatorsmentioning
confidence: 99%
“…In addition, potential quinazoline derivatives, as tumor-targeting drugs, target multiple receptors. A previous study has demonstrated that a newly synthesized phenylchloromethine-quinazoline derivative with SIRT1 as its target effectively promotes the apoptosis of hepatocellular carcinoma in vivo and in vitro [111].…”
Section: Potential Therapeutic Substances For Hcc-targeting Sirtsmentioning
confidence: 99%